1989
DOI: 10.23986/afsci.72374
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carcass temperature, glycogenolysis and glycolysis 45 min postmortem on the development of PSE pork

Abstract: This study investigated the effect of slaughter stress, scalding and process time from stunning to chilling on carcass temperature, muscle glycogen and lactate content, and the development of PSE meat (pH1≤5.8). Blood creatine kinase (CK) activity was positively (P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Handling of the pork carcass can also influence meat quality. Scalding and dehairing of the carcass to remove hair increases carcass temperature due to accelerated glycolysis (Honkavaara 1989b). These procedures increase the incidence of PSE because the rates of glycolysis and glycogenolysis and thus pH decline are increased while carcass temperature is high.…”
Section: Pale Soft and Exudative Porkmentioning
confidence: 99%
See 1 more Smart Citation
“…Handling of the pork carcass can also influence meat quality. Scalding and dehairing of the carcass to remove hair increases carcass temperature due to accelerated glycolysis (Honkavaara 1989b). These procedures increase the incidence of PSE because the rates of glycolysis and glycogenolysis and thus pH decline are increased while carcass temperature is high.…”
Section: Pale Soft and Exudative Porkmentioning
confidence: 99%
“…Postmortem anaerobic glycolysis is accelerated at high carcass temperatures and excessive lactic acid is produced. The resultant low ultimate pH (Troeger and Woltersdorf 1987;Honkavaara 1989b) as well the reduced pH at high body temperature leads to protein denaturation and produces the characteristic PSE muscle condition. Troeger and Woltersdorf (1987) suggested that muscle from skinned carcasses (compared to scalded) has improved muscle color and water holding capacity.…”
Section: Dehairingmentioning
confidence: 99%
“…However, no significant differences in 45-min temperature were detected (P > 0.05; Table 2). Previous studies have reported that the time spent from stunning to splitting had only a minor effect on carcass temperature (Honkavaara, 1989).…”
Section: Resultsmentioning
confidence: 83%
“…Scalding periods of up to 9 min may be needed for adequate hair removal (van der Wal et al, 1993). However, carcass temperature may increase during extended scalding (Honkavaara, 1989;van der Wal et al, 1993). Reducing the duration of scalding allows for earlier evisceration and entry into the cooler, which may minimize protein denaturation due to prolonged exposure to high muscle temperatures.…”
mentioning
confidence: 99%
“…If chilling is inadequate or delayed, the resulting pork will have an increased incidence of PSE regardless of the genotype of the pig (Honkavaara, 1989). Delayed chilling of poultry carcasses has also shown that the pH decline continued more rapidly and water loss increased with increasing time prior to chilling (Lesiak et al, 1996).…”
Section: Temperaturementioning
confidence: 99%